Dynamics of formation of ecosystem relationships in roadside landscapes of the left-bank part of Cherkasy region - Sonko, S. P.; Niezhentsev , A. S. (Man and Environment. Issues of Neoecology, 2026)
Purpose. A study of the dynamics of new ecosystems forming as a result of highway construction on sites that were once natural or anthropogenically altered landscapes, with a view to restoring future biodiversity. Methods. Field observation and photographic documentation, geochemical analysis, and instrumental monitoring. Results. The authors focused primarily on the ecosystemic aspect of the broader issue—the anthropogenic transformation of natural landscapes. This is because ruderal vegetation, which largely forms new ecotopes resulting from human activity, plays a restorative role for degraded substrates. It actively participates in biogeochemical processes and is a key factor in the restoration of native flora following its complete destruction due to road construction. An assessment was made of the differences between roadside ecosystems on the left bank of the Cherkasy region (Kaniv–Zolotonosha–Chornobai route) and local ecosystems. The greatest prevalence of species from the Asteraceae family was observed. In addition, the spread of invasive flora was recorded in all studied areas. At the same time, ruderal and native flora families along roadways jointly contribute to the formation of ecosystem connections. Polygons were identified where abnormal deviations in the studied indicators were observed. Conclusions. Roads function as habitats, sources, sinks, barriers and channels. As habitats, road corridors can support entire populations of plants and animals and may be important for their conservation. If they contain some of the last local or seed habitats of a species, they may be critically important. The study of individual parameters that characterize the formation of ecosystem ties in roadside landscapes of highways of the right bank of the Cherkasy region and the comparison of these parameters with the National Biotope Catalog allows us to establish certain patterns of the distribution of ruderal vegetation, which will subsequently form ecosystems resistant to external disturbances.